Palliative and end of life care for a child: Understanding parents' coping strategies. (2nd August 2020) - Darlington, Anne‐Sophie; Randall, Duncan; Leppard, Lisa; Koh, Michelle
Abstract: Aim: Understanding of coping strategies that parents use before the death of their child is crucial and will enable us to best provide support. The current study aimed to explore parents' coping strategies, and map these onto an existing theoretical framework. Methods: Bereaved parents and parents of a child with a life‐limiting/threatening condition were interviewed to investigate coping strategies, recruited through Intensive Care Units (2 Neonatal, 2 Paediatric, 1 Paediatric Cardiac) and a children's hospice. Analysis focused on coping strategies and mapping these onto the framework. Results: 24 parents of 20 children were interviewed and identified. Parents use a variety of coping strategies (n = 25) such as humour, staying positive, advocating and staying strong for others, expressing emotions and preparing, while also living life to the full, supported by others. The themes were successfully mapped onto the theoretical framework, which focuses on the constructs of approach and avoidance, as well as coping for self and others. Conclusion: The findings have provided a detailed account of the breadth and depth of coping strategies parents use, including those classed as avoidance. The strategies were successfully mapped onto the theoretical framework. Future research should investigate changes over times, and associations to negative long‐term outcomes.